Simulated intra-individual skin color changes and their impact on facial attractiveness across Japanese, Chinese, and Caucasian faces - Koizumi, Koyo; Nagashima, Megumi; Hirao, Naoyasu; Ohira, Hideki (Frontiers in Psychology, 2025)
IntroductionUnderstanding the influence of facial features on attractiveness is important for the development of cosmetics that improve attractiveness. Although it is known that changes in skin color affect attractiveness, few studies have investigated whether changes in skin color within individuals affect attractiveness, or whether these effects vary across geographic and cultural contexts. Therefore, through online surveys, we aimed to investigate changes in visual attractiveness due to intra-individual changes in skin color, using images of Japanese, Chinese, and Caucasian faces.MethodTen patterns of skin color change were applied to the average faces of Japanese, Chinese, and Caucasian men and women in their 20s. Using online surveys,1,200 Japanese, 1,518 Chinese, and 1,200 Italian participants were asked to rate the attractiveness of the facial images on a 5-point Likert scale.ResultsChanges in attractiveness associated with changes in skin color were observed in all surveys. Furthermore, we found geographic, cultural, and sex differences in changes in attractiveness associated with changes in skin color.ConclusionThe results indicate that intra-individual changes in skin color can alter facial attractiveness. Furthermore, changes in attractiveness in response to skin color changes may vary according to facial sex and geographic and cultural backgrounds.